RETRACTED: Li et al. Influences of Cr(VI) on SOD Activity, MDA, and MT Content in the Hepatopancreas and Gill of Portunus trituberculatus. Fishes 2024, 9, 407 - Lei Li; Chenshan Shao; Guodong Xv; Linlan Lv; Jiacheng Jiang; Weiyi Zou; Weiwei Su; Yanming Sui; Mei Jiang (Fishes, 2025)
The journal retracts the article titled “Influences of Cr(VI) on SOD Activity, MDA, and MT Content in the Hepatopancreas and Gill of Portunus trituberculatus” [...]

RETRACTED: Influences of Cr(VI) on SOD Activity, MDA, and MT Content in the Hepatopancreas and Gill of Portunus trituberculatus - Lei Li; Chenshan Shao; Guodong Xv; Linlan Lv; Jiacheng Jiang; Weiyi Zou; Weiwei Su; Yanming Sui; Mei Jiang (Fishes, 2024)
The toxic effect and differences of Cr(VI) on superoxide dismutase (SOD) activity, MDA, and metallothionein (MT) content in the hepatopancreas and gill of Portunus trituberculatus were investigated during Cr(VI) enrichment (15 days) and release experiments (15 days). Results showed that the 1.50 and 0.30 mg/L test groups significantly exhibited higher SOD, MDA, and MT content in the hepatopancreas and gill compared with the control group after 15 days of enrichment (p 0.05). The gill of P. trituberculatus achieved the highest SOD activity, MDA, and MT content earlier than the hepatopancreas, but the highest values were lower. The gill showed a shorter recovery time than the hepatopancreas. We concluded that the gill of P. trituberculatus exhibited a more rapid response to, and recovery from, Cr(VI) exposure compared to the hepatopancreas, making it a more sensitive tissue for assessing Cr(VI) toxicity, though both tissues showed a capacity for recovery after the removal of the contaminant.

Reliability analysis of three-dimensional reinforced slope considering the spatial variability in soil parameters - Yuke Wang; Linlan Shao; Yukuai Wan; Hao Chen (Stochastic Environmental Research and Risk Assessment, 2024)